Parent school program based on technology: randomızed controlled trıal protocol - Ebru Kılıçarslan Törüner; Ahu Çırlak (Selcuk University, 2023)
Objective: The purpose of this study was to assess the efficacy of a technology-based parent school program designed for parents of children aged 1-3 to improve their parenting abilities. Method: The research is a parallel-group, single-blind (participant) randomized controlled trial. The research will be conducted with parents with children aged 18 and 24 months in a hospital's well-child outpatient clinic in Turkey. The data of the research will be collected with Parent and Child Descriptive Data Form, Parenting Skill Assessment Form, Skill Assessment Form the Toddler Development, Development of the Psychosocial Status Assessment Form for Parents (1-3 aged), and The Self-Efficacy for Parenting Tasks Index-Toddler Scale (SEPTI-TS) (1-3 years). The minimum sample size of the research is planned to be a total of 68 participants (intervention group=34, control group=34). The program will last 10 weeks. Parents in the intervention group will read the modules on the website and then participate in the online group interaction. Parents will receive counseling throughout the program. In addition, motivational messages will be sent to parents during the follow-up phase. The modules will deal with the child's physical growth, cognitive and language development, and social-emotional development. The modules will be aided by videos and messages. This study was planned based on Meleis' Transition Theory. Results: Following the Technology-Based Parent School Program, parents are expected to have child-rearing skills and self-efficacy in terms of the development of their children. Usage in practice: The parent school will be a guide to support parents in physical, cognitive, social-emotional, and language development of the 1-3-year-old child.